Letter : Spanish seamen - Schevenels, Walther, b. 1894
025a-0080-001 INTERNATIONAL FEDERATION OF TRADE UNIONS IFTU 9, AVENUE D'ORSAY, PARIS-VIIe Sch/H TELEGRAMS : INTERFED-PARIS TELEPHONE : INVALIDES 45-88 AFFILIATED COUNTRIES : ARGENTINE AUSTRIA BELGIUM CANADA CZECHOSLOVAKIA DANTZKIG DENMARK DUTCH EAST INDIES ESTONIA FINLAND FRANCE GREAT BRITAIN GREECE HOLLAND HUNGARY INDIA LUXEMBURG MEMEL TERRITORY MEXICO NORWAY PALESTINE POLAND ROUMANIA SOUTH AFRICA SOUTH-WEST AFRICA SPAIN SWEDEN SWITZERLAND YUGOSLAVIA EXECUTIVE COMMITTEE : President : W. M Citrine, Great Britain Vice-Presidents: H. Jacobsen, Denmark; L. Jouhaux, France; E Kupers, Holland; Corn. Mertens, Belgium; R Tayerle, Czechoslovakia General Secretary : W Schevenels Letter Sec. ref. div. No. 1123 24th August, 1939. Mr. H. V. Tewson, LONDON. Dear Comrade Tewson, SPANISH SEAMEN I have carefully noted what you say in your letter of the 16th August, regarding the Spanish seamen in England who want to emigrate to Mexico or other Latin American countries, and as soon as possible I will approach the UGT in this matter, since it has much more influence in the SERE than I have, and will ask it to press for arrangements to be made for the very early departure of these refugees. Yours sincerely, W. Schevenels, General Secretary: EAB 292/946/25a/80